2015
DOI: 10.1002/prot.24931
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced structural transition of mature HIV‐1 protease from a combined NMR/MD simulation approach

Abstract: We investigate the pressure-induced structural changes in the mature human immunodeficiency virus type 1 protease dimer (HIV-1 PR), using residual dipolar coupling (RDC) measurements in a weakly oriented solution. 1DNH RDCs were measured under high-pressure conditions for an inhibitor-free PR and an inhibitor-bound complex, as well as for an inhibitor-free multidrug resistant protease bearing 20 mutations (PR20). While PR20 and the inhibitor-bound PR were little affected by pressure, inhibitor-free PR showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…To follow quantitatively the transition of secondary structures of silk fibroin under pressure, a curve-fitting analysis must be employed. Prior to curve fitting, the number of bands under the band profile in the region of 1700-1600 cm 21 were resolved by secondary derivative and Fourier self-deconvolution analyses, as shown in Figures 2 and 3. The bands resolved by these analytical methods were presented in Table 1, and these five bands were used to fit the time-dependent IR spectra in Figure 1.…”
Section: Kinetics Of Conformational Transitions Of Silk Fibroin In mentioning
confidence: 99%
See 1 more Smart Citation
“…To follow quantitatively the transition of secondary structures of silk fibroin under pressure, a curve-fitting analysis must be employed. Prior to curve fitting, the number of bands under the band profile in the region of 1700-1600 cm 21 were resolved by secondary derivative and Fourier self-deconvolution analyses, as shown in Figures 2 and 3. The bands resolved by these analytical methods were presented in Table 1, and these five bands were used to fit the time-dependent IR spectra in Figure 1.…”
Section: Kinetics Of Conformational Transitions Of Silk Fibroin In mentioning
confidence: 99%
“…In addition to chemical factors, 5,6 physical factors, especially the hydrostatic pressure in silkworm glands may also play an important role. 7 Although a large amount of literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] reported the influence of high hydrostatic pressure on the conformational transitions of many other proteins, no investigation on the effect of pressure on silk fibroin has been found so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recent backbone residual dipolar couplings measured for the N-H amide vectors confirmed that PR20 adopts a wide-open flap conformation in solution 17 . Using a combined NMR/MD approach we also showed that pressure perturbation induces the opening of the glycine-rich flaps of the inhibitor-free PR, while no such effect was detected for the inhibitor-free PR20 18 at subdenaturing pressure, therefore confirming that drug-resistance mutations affect the open-closed flap equilibrium of the PR dimer.…”
Section: Introductionmentioning
confidence: 68%
“…These results clearly demonstrate that in contrast to the inhibitor-free PR D25N , PR20 D25N unfolds in a highly cooperative manner, closely approximating an ideal two-state transition. In the absence of inhibitor at atmospheric pressure, PR D25N dimer was shown to adopt a closed conformation with very transient opening of the flaps 42 , while PR20 D25N adopts mostly an open flap conformation in solution 17,18 . Based on the present results, we hypothesize that decreased cooperativity observed for unfolding of the inhibitor-free PR D25N reflects a three-state unfolding transition: closed-flap → open-flap → unfolded, while PR20 D25N undergoes a simple two-state transition: open-flap → unfolded (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Amber 99SB and general amber force field (GAFF) [3941] were used for CDK8/CycC and the nine ligands, respectively. Single protonation states were used for all histidine residues according to predictions from comparing results for MCCE [42, 43], ProPKa [44, 45], and DelPhiPKa [46, 47]. Six Cl − ions were placed to maintain a neutral system.…”
Section: Methodsmentioning
confidence: 99%